Lentes de contacto refractivos y su incidencia en la calidad visual y desempeño laboral del personal de la unidad de policía comunitaria Montalvo, Provincia Los Ríos, primer semestre del 2018 - Coloma Abril, Viviana Jaqueline (2018)
Currently there is a wide variety of diseases that directly affect the health of the eyes, some are treated by surgical treatments and others with alternative treatments, it is then in this scenario is where contact lenses come into play. Contact lenses that exist today, in their different types, designs and materials, allow us to cover, almost completely all ranges of graduations, in addition to visual problems associated with injuries, side effects, refractive postsurgery (scleral lenses), therapies associated with optometric treatments (amblyopia). Every day it becomes more important to know and understand other people the importance of visual health and the important role of good visual care, that is why this time the general objective will be "Establish techniques with appropriate procedures on the visual defects in order to improve the visual quality and work performance in the Montalvo Community Policing Unit ". To carry out the whole project, a deductive method was implemented that allowed to find the problems derived from a general problem, by means of a field investigation since there was a direct observation of the object of study, at the same time a series of surveys and checks were applied. visuals to obtain results and conclusions. Regarding results and conclusions, it was found that there were cases of police officers who presented untreated visual complaints and others who wore frame lenses but this interfered in their daily police work, so they were explained the benefits, care and use of contact lenses as required in each case, so that their work tasks were not hindered.